Adoption of open innovation strategies among SMEs: a comparative study In Portugal and Turkey - Rahman, Md. Hakikur (2013)
The aim of this paper is to outline the situation of the Portuguese and the Turkish small and medium scale enterprises (SMEs) in the field of adopting various open innovation strategies. Through the research, the reader may get a bird sight view on the conditions of the decision-making process leading to the introduction of a open innovation among SMEs within the local context. In the aspect of adoption of strategies the Portuguese enterprises adopt collaboration with universities in higher proportion, while Turkish SMEs adopt collaboration with intermediaries in higher proportion, though in both countries, collaboration with other partners remain as the best chosen strategy. It has been concluded that enterprises of the same size in the surveyed countries consider similar factors before making a decision on introducing open innovation strategies in their business. Furthermore, it is expected that within a short time, an extended survey will be carried out in both countries, including one or two additional countries.